Assessment of Quality of Nurses’ Work Life in Tertiary Care Hospitals of Peshawar, Khyber Pakhtunkhwa, Pakistan: Assessment of Quality of Nurses Work Life - Rahim, Tariq; Ayub, Ayaz; Shah, Bakhtiar Ali; Khan, Ejaz Ali; Sajid, Nadia (Pakistan Journal of Health Sciences, 2023)
Nurses have been considered the backbone of health care delivery system, but regretfully saying that very limited attention has been paid to the development of nursing throughout the world. Objective: To assess the Quality of Nurses Work Life (QNWL) in Tertiary Care Hospitals of Peshawar Pakistan. Methods: Descriptive cross-sectional approach was applied to assess the QNWL in Lady Reading Hospital and Hayatabad Medical Complex Peshawar. Sample consisted of 240 participants via selection of multistage random sampling technique. Brook QNWL questionnaire was adopted for data collection and then validated and pre-tested it. Results: The sample data consisted of 79.20% female 20.80% male participants, out of which 46.02% were married and 53.98% un-married. The sample consisted of 94.25% Charge Nurses, 4.42% Head Nurses and 1.33% Nursing Managers in the study. The mean score of QNWL in this study was 162.24 ± 21.16. Furthermore, 3.98% nurses reported Low QNWL, 92.48% Moderate QNWL and 3.54% High QNWL in the sample. There was found an association between employment type with home life and work load subscales of QNWL whereas, home life has also an association with gender, marital status and salaries. Conclusions: It was concluded from the study findings that majority (92.48%) nurses have moderate QNWL in selected hospitals. Nurses home life and work load subscale of QNWL is affected by some demographics. Therefore, the study findings suggest recommendations in home life and work load management for policy makers in order to enhance QNWL in Tertiary Care Hospitals of Peshawar Pakistan.